The Law Liability of Non-Judicial Mediators in Land Right Disputes - Yahman (Acta Universitatis Carolinae. Iuridica)
Land disputes are one of the most common cases in Indonesia. It is due to the demand for land ownership rights. In this case, mediation is used to resolve the case. The non-judicial mediator is a neutral party who helps the parties fairly. This study examines the civil law liabilities of non-judicial mediators in land ownership disputes and the legal position of a non-judicial mediator on authentic peace deeds. This research applied a juridical-normative approach with a law and a conceptual approach. The results indicated that non-judicial mediators, in carrying out their primary duties, both in terms of rights and obligations, must be based on law and protected by law to optimally provide services to the community while having a clear legal position in the notary. To sum up, unifying the mediation arrangement in one statutory regulation and mediation in the realm is necessary, both in litigation and non-litigation. In addition, future research can investigate the effectiveness and implementation of mediation certification, secrecy, financing, and repetition of mediation in land dispute cases. Further exploration is needed to understand the impact of mediation on the autonomy of the parties involved in land ownership disputes.